2008
DOI: 10.1038/labinvest.2008.47
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3-like-1 enhances bacterial adhesion to colonic epithelial cells through the interaction with bacterial chitin-binding protein

Abstract: Dysregulated host/microbial interactions play a pivotal role in the pathogenesis of inflammatory bowel disease. We previously reported that chitinase 3-like-1 (CHI3L1) enhances bacterial adhesion and invasion on/into colonic epithelial cells (CECs). In this study, we designed to identify the exact mechanism of how CHI3L1 enhances the bacterial adhesion on CECs in vitro. As compared with wild type (WT) of Serratia marcescens, chitin binding protein (CBP) 21 knockout strain of S. marcescens significantly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 34 publications
2
79
0
1
Order By: Relevance
“…Consistent with this idea, chiA mutants of other species of Enterobacteriaceae are less able to attach to epithelial cells in vitro (52). The N terminus of GbpA from Vibrio cholerae shares ϳ50% amino acid sequence identity with Cbp21 of S. marcescens; mutation of the genes for these polysaccharide binding proteins conferred a reduction in attachment to epithelial cells in vitro (54,55). Therefore, it is possible that the chitinases and chitin binding proteins controlled by EepR contribute to pathogenesis under certain circumstances.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with this idea, chiA mutants of other species of Enterobacteriaceae are less able to attach to epithelial cells in vitro (52). The N terminus of GbpA from Vibrio cholerae shares ϳ50% amino acid sequence identity with Cbp21 of S. marcescens; mutation of the genes for these polysaccharide binding proteins conferred a reduction in attachment to epithelial cells in vitro (54,55). Therefore, it is possible that the chitinases and chitin binding proteins controlled by EepR contribute to pathogenesis under certain circumstances.…”
Section: Discussionmentioning
confidence: 88%
“…The expression of YKL-40 is highly induced in colonic epithelial cells and macrophages in areas with intestinal inflammation and enhances potentially pathogenic, but not nonpathogenic, bacterial adhesion, and invasion into colonic epithelial cells (17,18). It has been suggested that growth-stimulating effects of epithelial YKL-40 in response to inflammatory or stressful stimuli are a critical and physiologic function in remodeling and maintaining the basic architecture of intestinal epithelium (25). Furthermore, the chitin-binding motif of YKL-40 is specifically associated with activation of Akt signaling in colonic epithelial cells, enhances the secretion of the proinflammatory cytokines IL8, and TNFa, and promotes proliferation of colonic epithelial cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Peroxiredoxin 1 (a 2-Cys-peroxiredoxin), secreted from tumor cells (22), was shown previously to induce proinflammatory cytokines in macrophages via interactions with Toll-like receptor 4 and to promote chronic inflammation, which could support tumor growth (28). Regarding chitinases, it is now clear that some inflammatory conditions of the gastrointestinal (GI) tract (inflammatory bowel disease [IBD] and ulcerative colitis [UC]) lead to the induction of host cell chitinases by triggering the increased uptake of intracellular bacteria by colonic cells (16,17) and in potentiating the development of epithelial tumorigenesis (8). Considering that some symptoms of CDAD resemble those of both IBD and UC, C. difficile chitinase may play a direct role in infection and not simply in macromolecular degradation.…”
Section: Discussionmentioning
confidence: 99%